Impact of ergonomics on work performance in the manufacturing industry: A systematic review - Campos-Naval, Jose Elvis; Castañeda-López, Victor Alonso; Aparicio-Ballena, Jorge Alberto (LACCEI, 2025)
This systematic review analyzes the influence of ergonomics on work performance in the manufacturing sector. Ergonomics, which emerged in the 1940s, has established itself as a fundamental discipline for adapting work environments to human capabilities. Its correct implementation not only prevents musculoskeletal injuries, but also increases efficiency and improves work excellence and employee well-being. From detailed research in sources such as Scopus, 36 relevant studies published between 2014 and 2024 were included, which provide solid evidence on how ergonomic interventions can positively transform working conditions. The findings indicate that poor application of ergonomic principles can lead to health conditions, such as muscle discomfort and high levels of stress, which negatively impact work efficiency. It was identified that most studies focus on large manufacturing industries, where lower back and upper extremity injuries are common. To analyze performance in the work environment, the most commonly used tools were questionnaires and performance records, which have proven to be effective in detecting ergonomic risks. In addition, the relevance of applying ergonomic adjustments based on scientific studies to improve working conditions is emphasized. In short, a correct ergonomics management not only favors the health of workers, but also strengthens the profitability and sustainability of companies in the manufacturing sector.